Early Detection of Hypertension Education Through the PPCU 90-DayHealth Program in Loa Raya Village - Ni Luh Ayu Ekayanti; Octa Ida Manullang; Alya Indriani; Derajat; Alfina Dwi Anggraini; Desy Anugerah Rahmayanti; Siswanto Anugerah Rahmayanti (Mulawarman International Conference on Tropical Public Health, 2025)
disease that often goes unnoticed until complications occur. In Loa Raya Village, many pre-elderly and elderly residents experience high blood pressure without realizing it. The lack of awareness and persistence of unhealthy habits highlight the need for community-based education. This study aimed to improve knowledge, awareness, and preventive behavior toward hypertension among pre-elderly and elderly individuals in Loa Raya Village. By integrating the Personal Prevention Check-Up (PPCU) with the 90-Day Health Program, the community was encouraged to identify their risk levels and adopt healthy habits, including balanced nutrition, regular exercise, and stress management. A cross-sectional survey was conducted using the PPCU form through structured interviews at the elderly health post and door-to-door visits. Participants aged 45 years and above were selected purposively. Of 50 participants, 32 were at high risk, 12 moderate, and 6 low risk. The program increased awareness of hypertension, early detection, and healthy living practices. Implementers also learned the value of empathetic communication and continuous community engagement. Integrating PPCU with the 90-Day Health Program effectively raised awareness, promoted healthy behavior, and provided a practical, low-cost model for preventing non-communicable diseases in rural communities.